Neighborhood quality and student performance - Felix Weinhardt (Institute for the Study of Labor (IZA), 2013)
Children who grow up in deprived neighborhoods underperform at school and later in life but whether there is a causal link remains contested. This study estimates the effect of very deprived neighborhoods, characterized by a high density of social housing, on the educational attainment of fourteen years old students in England. To identify the causal impact, this study exploits the timing of moving into these neighborhoods. I argue that the timing can be taken as exogenous because of long waiting lists for social housing in high-demand areas. Using this approach, I find no evidence for effects on student performance.
Keywords: J18; I21; J24; 330; neighborhood effects; housing policy